1995
DOI: 10.3168/jds.s0022-0302(95)76863-1
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the Conjugated Linoleic Acid Contents of Dairy Products

Abstract: The objective of this research was to determine the content of conjugated linoleic acid, an anticarcinogen, in dairy products. Fifteen cheeses, three fermented dairy products (other than cheeses), and four fluid milk products (two brands for each product) were included in the survey. Total lipids, fatty acids, protein, moisture, and titratable acidity were also measured to determine the relationship between the content of these constituents and conjugated linoleic acid content. The conjugated linoleic acid con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
174
4
18

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(209 citation statements)
references
References 15 publications
13
174
4
18
Order By: Relevance
“…Milk lipids constitute the principal dietary source of dietary CLA (Lin et al, 1995). Studies of cell lines have shown that CLA inhibits the proliferation of colorectal, breast and skin tumour cells (Parodi, 1997), mammary tumorigenesis in rats (Ip & Scimeca, 1997) and decreases the number of aberrant crypt foci in rats on 2-amino-3-methylimidazo [4,5-f] quinoline-induced colon carcinogenesis (Liew et al, 1995).…”
Section: Fatsmentioning
confidence: 99%
“…Milk lipids constitute the principal dietary source of dietary CLA (Lin et al, 1995). Studies of cell lines have shown that CLA inhibits the proliferation of colorectal, breast and skin tumour cells (Parodi, 1997), mammary tumorigenesis in rats (Ip & Scimeca, 1997) and decreases the number of aberrant crypt foci in rats on 2-amino-3-methylimidazo [4,5-f] quinoline-induced colon carcinogenesis (Liew et al, 1995).…”
Section: Fatsmentioning
confidence: 99%
“…In human studies often not the same effects suggested based on animal studies are found. The CLA content in dairy products was 0.338 to 0.796 g·100 g -1 lipid in a survey of 22 different dairy products and cheeses from a supermarket in Pullmann, Washington [41]. Collomb et al [11] found in a study of 44 milk samples from three different regions in Switzerland (lowlands, mountains and highlands) CLA concentrations of 0.87, 1.61 and 2.36 g·100 g -1 lipid, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1 The major dietary source of CLA for humans is ruminant meats, such as beef, lamb and dairy products including milk and cheese. 2,3 The major isomer of CLA in natural foods is cis-9, trans-11 (c9t11). 4,5 Research on the biological functions and health benefits of CLA dates back to the 1980s when Ha et al 6 made the seminal observation that CLA mixtures isolated from grilled beef or from a base-catalyzed isomerization of linoleic acid, inhibited chemically induced skin neoplasia in mice.…”
Section: Introductionmentioning
confidence: 99%